2018
DOI: 10.1016/j.envpol.2017.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Benzoylecgonine exposure induced oxidative stress and altered swimming behavior and reproduction in Daphnia magna

Abstract: Several monitoring studies have shown that benzoylecgonine (BE) is the main illicit drug residue commonly measured in the aquatic system worldwide. Few studies have investigated the potential toxicity of this molecule towards invertebrate and vertebrate aquatic non-target organisms focusing on effects at low levels of the biological organization, but no one has assessed the consequences at higher ones. Thus, the present study was aimed at investigating the toxicity of a 48-h exposure to two concentrations of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 62 publications
2
39
0
1
Order By: Relevance
“…Nunes et al [66] previously reported that no significant effect on GPx activities was observed in A. salina after exposure to sodium dodecyl sulfate and diazepam, whereas the exposure to clofibric acid and clofibrate reduced the activity as test concentration increased. Nevertheless, exposure of D. magna to benzoylecgonine (cocaine metabolite) increased the GPx activity by 1.7-fold and raised the swimming activity [68].…”
Section: Glutathione Peroxidasementioning
confidence: 99%
See 3 more Smart Citations
“…Nunes et al [66] previously reported that no significant effect on GPx activities was observed in A. salina after exposure to sodium dodecyl sulfate and diazepam, whereas the exposure to clofibric acid and clofibrate reduced the activity as test concentration increased. Nevertheless, exposure of D. magna to benzoylecgonine (cocaine metabolite) increased the GPx activity by 1.7-fold and raised the swimming activity [68].…”
Section: Glutathione Peroxidasementioning
confidence: 99%
“…Similarly, tramadol enhanced GPx activity in our bioassays at warmer conditions, but it reduced the overall swimming activity of A. salina. Not only the contaminant, but also its metabolites (e.g., cocaine metabolites) are involved in the activation of redox cycles, depletion, and decrease of antioxidant enzymes leading to the overproduction of reactive oxygen species and oxidative stress conditions [68]. For this reason, it would be fascinating to evaluate in future studies the metabolization of tramadol in A. salina and the possible effects of its metabolites (O-desmethyltramadol and N-desmethyltramadol) on survival and enzymatic.…”
Section: Lactate Dehydrogenasementioning
confidence: 99%
See 2 more Smart Citations
“…The ability to move and escape from contaminants might determine the spatial distribution of organisms and the migration behavior (Gray ; Åtland and Barlaup ; Hansen et al ) and, consequently, affect the ecosystem's dynamics and functioning (Hidaka and Tatsukawa ; Schiesari et al ). For instance, behavior related to movement patterns has been used with Daphnia magna as an early warning of environmental disturbance by online biomonitoring (Ren et al ; Cano et al ; Parolini et al ). For snails, behavioral endpoints such as activity (time to start a normal movement), immobility (Alonso and Camargo ), burying (Hampel et al ), and retraction within the shell (Hellou et al ) have been used as ecotoxicological responses.…”
Section: Spatial Avoidance and Habitat Preference Versus Behavioral Ementioning
confidence: 99%